State and local public finance - Fisher, Ronald C. (New York Routledge, 2023)
State and Local Public Finance provides a comprehensive and sophisticated analysis of state and local government public finance practices and issues, using the basic tools of economics.
Keywords: Finance and Economy Sector; Microeconomic Analysis; Tax Analysis